2017
DOI: 10.1186/s13054-017-1670-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pathophysiology of hypoxic ischemic brain injury after cardiac arrest: a “two-hit” model

Abstract: Hypoxic ischemic brain injury (HIBI) after cardiac arrest (CA) is a leading cause of mortality and long-term neurologic disability in survivors. The pathophysiology of HIBI encompasses a heterogeneous cascade that culminates in secondary brain injury and neuronal cell death. This begins with primary injury to the brain caused by the immediate cessation of cerebral blood flow following CA. Thereafter, the secondary injury of HIBI takes place in the hours and days following the initial CA and reperfusion. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
296
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(335 citation statements)
references
References 74 publications
3
296
0
3
Order By: Relevance
“…26 It after cardiac arrest is a leading reason for long-term neurologic disability and mortality in survivors and its pathophysiology encompasses a various cascade that can culminate in neuronal cell death and secondary brain injury. 27 Thus, in this study, we were supposed to explore the role of miR-129-5p in neuroprotective effect of DEX on HIBI by targeting COL3A1 through the Wnt/β-catenin signaling pathway in neonatal rats. Initially, our study revealed that the DEX + XAV-939 and DEX + miR-129-5p mimics groups had elevated weight, active avoidance rate, correct reaction rate, and weight rate of cerebral hemisphere (left/right), but decreased death rate, total reaction frequency and time, and water content of left cerebral hemisphere as compared with the DEX, DEX + NC and DEX + miR-129-5p inhibitors + XAV-939 groups.…”
Section: Discussionmentioning
confidence: 99%
“…26 It after cardiac arrest is a leading reason for long-term neurologic disability and mortality in survivors and its pathophysiology encompasses a various cascade that can culminate in neuronal cell death and secondary brain injury. 27 Thus, in this study, we were supposed to explore the role of miR-129-5p in neuroprotective effect of DEX on HIBI by targeting COL3A1 through the Wnt/β-catenin signaling pathway in neonatal rats. Initially, our study revealed that the DEX + XAV-939 and DEX + miR-129-5p mimics groups had elevated weight, active avoidance rate, correct reaction rate, and weight rate of cerebral hemisphere (left/right), but decreased death rate, total reaction frequency and time, and water content of left cerebral hemisphere as compared with the DEX, DEX + NC and DEX + miR-129-5p inhibitors + XAV-939 groups.…”
Section: Discussionmentioning
confidence: 99%
“…These two previous studies [1,2] underlined the importance of preventing secondary cerebral injury after cardiac arrest and the role of arterial carbon dioxide on cerebral blood flow modulation in this. As described by Adrie and colleagues [3], cardiac arrest and sepsis have physiopathological similarities, including similar therapeutic interventions.…”
mentioning
confidence: 94%
“…In the July 31 issue of Critical Care, Eastwood and colleagues [1] discussed the discordant results of the potential therapeutic role of mild hypercapnia in the early post-resuscitation period observed by Sekhon and colleagues [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SCA frequently leads to prolonged hospitalization and is highly fatal with a mortality rate of approximately 90%. The leading cause of morbidity and mortality in SCA is profound neurologic injury, primarily due to lack of cerebral circulation during the arrest period, followed by secondary insults such as cerebral edema, reperfusion injury and hyperthermia [2]. SCA most commonly occurs outside of the hospital where mortality is significantly worse than in patients who suffer SCA inside a hospital [1,3].…”
Section: Introductionmentioning
confidence: 99%